Respuesta :
4x^4+x3-2x^2-6x+2
step by step:
(1): "x2" was replaced by "x^2". 2 more similar replacement(s).
2. ((((4•(x4))+(x3))-2x2)-6x)+2 (equation at the end of step 1)
3. equation at the end of step 2:
(((22x4 + x3) - 2x2) - 6x) + 2
4. polynomial roots caclulator:
3.1 Find roots (zeroes) of : F(x) = 4x4+x3-2x2-6x+2
Polynomial Roots Calculator is a set of methods aimed at finding values of x for which F(x)=0
Rational Roots Test is one of the above mentioned tools. It would only find Rational Roots that is numbers x which can be expressed as the quotient of two integers
The Rational Root Theorem states that if a polynomial zeroes for a rational number P/Q then P is a factor of the Trailing Constant and Q is a factor of the Leading Coefficient
In this case, the Leading Coefficient is 4 and the Trailing Constant is 2.
final result:
4x4 + x3 - 2x2 - 6x + 2
step by step:
(1): "x2" was replaced by "x^2". 2 more similar replacement(s).
2. ((((4•(x4))+(x3))-2x2)-6x)+2 (equation at the end of step 1)
3. equation at the end of step 2:
(((22x4 + x3) - 2x2) - 6x) + 2
4. polynomial roots caclulator:
3.1 Find roots (zeroes) of : F(x) = 4x4+x3-2x2-6x+2
Polynomial Roots Calculator is a set of methods aimed at finding values of x for which F(x)=0
Rational Roots Test is one of the above mentioned tools. It would only find Rational Roots that is numbers x which can be expressed as the quotient of two integers
The Rational Root Theorem states that if a polynomial zeroes for a rational number P/Q then P is a factor of the Trailing Constant and Q is a factor of the Leading Coefficient
In this case, the Leading Coefficient is 4 and the Trailing Constant is 2.
final result:
4x4 + x3 - 2x2 - 6x + 2
6x - 2 + 2x = -2 + 4x + 8
Simplifying
6x + -2 + 2x = -2 + 4x + 8
Reorder the terms:
-2 + 6x + 2x = -2 + 4x + 8
Combine like terms: 6x + 2x = 8x
-2 + 8x = -2 + 4x + 8
Reorder the terms:
-2 + 8x = -2 + 8 + 4x
Combine like terms: -2 + 8 = 6
-2 + 8x = 6 + 4x
Solving
-2 + 8x = 6 + 4x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-4x' to each side of the equation.
-2 + 8x + -4x = 6 + 4x + -4x
Combine like terms: 8x + -4x = 4x
-2 + 4x = 6 + 4x + -4x
Combine like terms: 4x + -4x = 0
-2 + 4x = 6 + 0
-2 + 4x = 6
Add '2' to each side of the equation.
-2 + 2 + 4x = 6 + 2
Combine like terms: -2 + 2 = 0
0 + 4x = 6 + 2
4x = 6 + 2
Combine like terms: 6 + 2 = 8
4x = 8
Divide each side by '4'.
x = 2
Simplifying
x = 2